Immunosenescence and severity of COVID-19. Issue 1 (1st December 2022) - Elhelw, Omar; Ragavan, Sharanniyan; Majeed, Waseem; Syed, Akheel
Abstract : Summary: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection causes coronavirus disease 2019 (COVID-19). It is associated with significant morbidity and mortality, and socio-economic disruption globally. Increasing age and ageing-associated comorbidities such as obesity, type 2 diabetes, and chronic cardiac, respiratory, kidney and liver diseases are associated with greater risk of adverse outcomes including severe illness, hospitalisation, intensive care admission and death. Older individuals are disproportionately affected regardless of pre-existing comorbidities. Ageing-related changes to the immune system results in a less effective response to novel pathogens. Atrophy of the thymus and a consequentially reduced T cell receptor (TCR) repertoire maybe responsible for the increasing severity of infection with advancing age, as T cells play a crucial role in viral clearance generally and in COVID-19. Vaccination programmes are currently gaining momentum and could potentially provide a route out of the pandemic. Relevance: Viral pandemics are not uncommon; H1N1, Ebola, Zika, SARS, Middle East respiratory syndrome (MERS) and now COVID-19 have been a significant cause of public disturbance, morbidity, and mortality over the past two decades. We are likely to continue to encounter novel viral pathogens increasingly commonly in the coming years. Medical students should therefore develop an understanding of the immune response to viruses and take this opportunity to familiarise themselves with the features of the COVID-19 pandemic. An appreciation of immunosenescence is also key as our communities continue to age. Take home messages: Symptoms of COVID-19 are heterogenous; individuals can be asymptomatic, have mild flu-like symptoms or severe respiratory disease and systemic complications. A potent T cell and B cell response is present with SARS-COV-2 infection, with antibodies targeting the viral spike protein. Immunosenescence is associated with a poorer response to novel and evolving pathogens. Vaccines show high efficacy against COVID-19 and mass vaccination programmes could be the route out of the pandemic.